STUDENTS’ OBSTACLES IN LISTENING COMPREHENSION IN TOEFL TEST - Surya Bayu Maulana; Diah Kurniati; Agung Dwi Nurcahyo (JELLT (Journal of English Language and Literature Teaching), 2022)
This research focuses on analyzing the students’ obstacles in listening comprehension during the TOEFL test. This present research aims (1) to find out what problems are faced by the students in listening comprehension and (2) to find the students’ strategies to overcome the problems faced in listening comprehension of English Education Department students of Universitas Muria Kudus. This qualitative case study is involving 53 participants who took the TOEFL course every semester in the academic year 2021/2022. The data was accumulated by using questionnaires and interviews. The result of the research showed that bad recording of the audio system during the listening section, the pace of the speakers when they speak, losing concentration, and the distraction from the non-technical side were the major obstacles in listening comprehension encountered by the students. This research also shows the strategies proposed by the students to enhance their listening skills. Despite the difficulty, the students agreed that listening comprehension skills are one of the most important skills that they had to learn as young learners because listening skills consist of language skills that they must master it. Knowing students’ obstacles to listening comprehension may help the teachers to propose and develop effective learning strategies, and also for the Lab UPT Bahasa to improve the quality of the audio system. The suggestion is made for marking the obstacles regarding how students could help themselves and all the parties could help their students to overcome the obstacles encountered by the students in listening comprehension.